Analisis Kebijakan Hukum terhadap Program Pemberdayaan Ekonomi dan Penanggulangan Kemiskinan di Kabupaten Lombok Tengah - Arief Purnama Ajie; Putu Ayu Thania Santosa; Andin Rusmini (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
This analysis aims to find out the strategies and steps used in community empowerment in Central Lombok Regency with literature review analysis helping to analyze previous studies which will provide suggestions and methods used in community empowerment in Central Lombok Regency. Using the descriptive qualitative method (literature review), this method will explain and describe the findings with descriptions. Data sources from several journal reference sources that are relevant to the topic of analysis. The focus of this analysis is community empowerment in Central Lombok district to reduce poverty. The results of the analysis show various methods and ways to achieve social prosperity, however, the implementation of empowerment must also pay attention to the geographical location of the community to provide a significant impact, such as empowerment in the tourism sector, arts and crafts sector or empowerment in other forms that provide benefits to the community. specially in the Central Lombok district, the empowerment that is often carried out is in the tourism sector for tourist villages and the use of social culture and local wisdom to help the community to attract tourists to visit and gain economic benefits.